2023
DOI: 10.1021/acs.est.3c02780
|View full text |Cite
|
Sign up to set email alerts
|

Change of Composition, Source Contribution, and Oxidative Effects of Environmental PM2.5 in the Respiratory Tract

Abstract: Fine particulate matter is a leading air pollutant, and its composition profile relates to sources and health effects. The human respiratory tract hosts a warmer and more humid microenvironment in contrast with peripheral environments. However, how the human respiratory tract impacts the transformation of the composition of environmental PM2.5 once they are inhaled and consequently changes of source contribution and health effects are unknown. Here, we show that the respiratory tract can make these properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…These findings suggest that organic redox-active compounds in PM 2.5 posed a primary oxidative hazard during monsoon. Furthermore, a recent study reported that the human respiratory tract can modify the composition of PM 2.5 by phasing out its semi-volatile nitrate and ammonium content, leading to a significant increase in the OP of inhaled PM 2.5 through enhanced metal solubility . This implies that the adverse health effects of oxidative stress from airborne PM 2.5 may be underestimated, necessitating further investigations, considering the influences of the respiratory tract and lung environment.…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggest that organic redox-active compounds in PM 2.5 posed a primary oxidative hazard during monsoon. Furthermore, a recent study reported that the human respiratory tract can modify the composition of PM 2.5 by phasing out its semi-volatile nitrate and ammonium content, leading to a significant increase in the OP of inhaled PM 2.5 through enhanced metal solubility . This implies that the adverse health effects of oxidative stress from airborne PM 2.5 may be underestimated, necessitating further investigations, considering the influences of the respiratory tract and lung environment.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Canadian forest wildfires serve as significant sources of air pollution in North America, with smoke particles transported into the CONUS airspace by atmospheric movements [55]. The northeastern and western coastal regions are major population and urban centers, yet PM2.5 accumulates continuously during this period, undoubtedly increasing health risks for local residents [56].…”
Section: Pm25 Prediction Over Conusmentioning
confidence: 99%
“…The atmosphere is one of the fundamental elements that humans rely on for survival and development [1,2]. Emerging studies have shown that long-term exposure to air pollutants, particularly PM2.5, increases the risk of respiratory and cardiovascular diseases [3][4][5]. PM2.5 primarily originates from human activities and is influenced by meteorological conditions [6][7][8].…”
Section: Introductionmentioning
confidence: 99%